Measuring Cerebrovascular Reactivity: Sixteen Avoidable Pitfalls - Sobczyk, Olivia; Fierstra, Jorn; Venkatraghavan, Lakshmikumar; Poublanc, Julien; Duffin, James; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Physiology, 2021)
An increase in arterial PCO2 is the most common stressor used to increase cerebral blood flow for assessing cerebral vascular reactivity (CVR). That CO2 is readily obtained, inexpensive, easy to administer, and safe to inhale belies the difficulties in extracting scientifically and clinically relevant information from the resulting flow responses. Over the past two decades, we have studied more than 2,000 individuals, most with cervical and cerebral vascular pathology using CO2 as the vasoactive agent and blood oxygen-level-dependent magnetic resonance imaging signal as the flow surrogate. The ability to deliver different forms of precise hypercapnic stimuli enabled systematic exploration of the blood flow-related signal changes. We learned the effect on CVR of particular aspects of the stimulus such as the arterial partial pressure of oxygen, the baseline PCO2, and the magnitude, rate, and pattern of its change. Similarly, we learned to interpret aspects of the flow response such as its magnitude, and the speed and direction of change. Finally, we were able to test whether the response falls into a normal range. Here, we present a review of our accumulated insight as 16 “lessons learned.” We hope many of these insights are sufficiently general to apply to a range of types of CO2-based vasoactive stimuli and perfusion metrics used for CVR.